EVALUATION OF INFORMATION MODELS BALANCED SCORECARD - Ivan Belousov (Вестник Северо-Кавказского федерального университета, 2022)
The article presents a comparative analysis of information technology based on the balanced scorecard. Examines both Russian and foreign software products. Analyzes the advantages, disadvantages and capabilities of each of the presented in the article of software products. On the basis of the data presented in the tables provides recommendations in the selection of software for effective management and optimization of the organization. To select the required software product, you must answer a few questions. Answering these questions can significantly simplify the choice. Unsuitable software products can be weeded based on the criteria below.